The Analysis Of Bela H. Banathy’s Model And Its Relevance To Islamic Education Learning In Schools - Hakim, Luqman; Jamil, Alvian Nur; Qomaruddin, Mochammad; Rifa'i, Ahmad Suzaki (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Learning Islamic religious education is an essential part of achieving national education goals. Meanwhile, choosing a learning model is important in achieving success in Islamic Religious Education. This research aims to reveal how applying the Bela H. Banathy learning model in Islamic religious education can improve the quality of learning. This qualitative research uses a literature study approach. The data analysis method uses descriptive analysis methods to reveal the application of the learning model developed in 1968 by Bela H. Banathy in learning Islamic religious education in schools. The research results show that the Bela H. Banathy learning system is relevant to learning Islamic religious education. This model uses an approach oriented towards student learning outcomes by developing the concept of a spiral or learning cycle. Implementation of this model is carried out through six stages, namely: (1) formulating goals, (2) developing tests, (3) analyzing learning activities, (4) designing a teaching system, (5) carrying out test development activities, (6) and making improvements based on Banathy's evaluation results. The Banathy model has advantages in formulating goals according to student abilities and a structured and measurable learning system. This model can provide meaningful learning experiences, improve critical thinking skills and creativity, and use a holistic learning approach. On the other hand, weaknesses include the need for more steps in designing learning and the tendency to ignore previously learned knowledge. Keywords: Learning Model, Bela H. Banathy, Islamic Religious Education